Cascade dams altered taxonomic and functional composition of bacterioplankton community at the regional scale - Jiang, Xufei; Liu, Yan; Zhou, Rixiu; Sun, Tianyi; Cao, Jingdan; An, Shuqing; Shen, Jiachen; Leng, Xin (Frontiers in Microbiology, 2023)
Dams are increasingly disrupting natural river systems, yet studies investigating their impact on microbial communities at regional scale are limited. Given the indispensable role of bacterioplankton in aquatic ecosystems, 16S rRNA gene sequencing was performed to explore how these communities respond to dam-influenced environmental changes at the regional scale in the Shaying River Basin. Our findings revealed that cascade dams create distinct environments, shaping bacterioplankton communities near the dams differently from those in natural rivers. In the upstream of the cascade dams, water quality was superior, while bacterioplankton community structure was simple with weak community interactions. In the midstream, nutrient and heavy metal content were increased, making bacterioplankton structures more susceptible to environmental changes. In the downstream of the cascade dams, water quality had a significant impact on the community and the bacterioplankton structures were highly complex. Additionally, environmental variables significantly influenced bacterioplankton functional groups. However, the response to these factors, as well as the interplay between functional and taxonomic diversity, varied markedly depending on the specific region of the cascade dams. We here delved into the effects of cascade dams on the taxonomic diversity and functional groups of bacterioplankton to provide a theoretical basis for segmentally regulating these dams.